2019
DOI: 10.1002/mp.13721
|View full text |Cite
|
Sign up to set email alerts
|

A Monte Carlo study on the PTW 60019 microDiamond detector

Abstract: Purpose Data on the output correction factor for small photon beam dosimetry of the microDiamond detector manufactured by the company PTW can be found in a variety of papers. Referring either to measurements or to Monte Carlo (MC) calculations, they show substantial disagreements particularly at very small fields. This work reports results of a further MC study aiming at a better understanding of how specific properties of the microDiamond detector are influencing its output correction factor and whether this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 34 publications
0
14
0
2
Order By: Relevance
“…()) and D¯mDD,MP3 is the dose to the mDD sensitive volume, both in the complete experimental setup. As done in our previous work, 10 and similar to the approach of several authors, 35–39 the factor f was decoupled into two sub‐factors, here named f E (energy dependence correction factor) and f V (volume‐averaging correction factor):fr,θ=fEr,θfVr,θ.…”
Section: Methodsmentioning
confidence: 99%
“…()) and D¯mDD,MP3 is the dose to the mDD sensitive volume, both in the complete experimental setup. As done in our previous work, 10 and similar to the approach of several authors, 35–39 the factor f was decoupled into two sub‐factors, here named f E (energy dependence correction factor) and f V (volume‐averaging correction factor):fr,θ=fEr,θfVr,θ.…”
Section: Methodsmentioning
confidence: 99%
“…Marinelli et al (2016) showed that the actual dimensions were close to the nominal ones, but the discussion encouraged the manufacturer to update blueprints by including all metallic structures (the supporting pins and contacts). It did not affect MC-calculated small-field correction factors (Hartmann and Zink 2019), but had implications for our study. The k Q,Q0 values given in Paper I were calculated using complete blueprints.…”
Section: Contributions Of Our Research 41 Synthetic Diamond Detector For Dosimetry In 192 Ir Brachytherapymentioning
confidence: 71%
“…Moreover, the detector's electron density is different from the water ones, thus perturbing the secondary electron field (density effect) [3]. Quantification and correction of the combination of volume averaging and density effects (volume effect), can be addressed using MonteCarlo simulation to calculate correction factors to relate the detector's signal to the dose in water [4,5]. Therefore, volume averaging with source occlusion and lack of lateral electron equilibrium can cause a reduction of linac output and of measured output.…”
Section: Introductionmentioning
confidence: 99%